An unusual cause of recurrent vomiting - Hsu, Yu-Chun; Yen, Hsu-Heng (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Hsu YC, Yen HH. An unusual cause of recurrent vomiting. Turk J Gastroenterol 2019; 30(12): 1062-3.